2016
DOI: 10.5539/mas.v10n6p188
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Optimism and Life Expectancy with Family Function among Parents with Disabled Children

Abstract: This study was done aimed to investigate the relationship between optimism and life expectancy with family function among parents with disabled children in the city of Tehran. This research is descriptive by correlation method. Statistical population included all parents with disabled children in Tehran and the research sample consisted of 202 people. Sampling method was chosen based on available. The Spss software version 18 and correlation method and simultaneous multiple regression was used to analyze the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It has become very important to perform research about instruments aimed to measure optimism in a valid and reliable manner since optimism is a psychological characteristic associated with many beneficial effects on many spheres of peoplés lives (see a very complete recent review of this topic in Carver & Scheier, 2014), for instance, physical and mental health (Conversano, Rotondo, Lensi, Della-Vista, Arpone, & Reda, 2010), interpersonal relationships (Sumi, 2006), family life (Esfahan & Rostami, 2016; Taylor, Larsen-Rife, Conger, Widaman, & Cutrona, 2010), professional life (Mishra, Patnaik, & Mishra, 2016), and the development of an overall sense of social well-being (Yu & Luo, 2018), More specifically, from a medical perspective, evidence shows that optimism decreases the level of anxiety and depression in cancer patients (Ahmad & Gaber, 2019; Lam et al., 2016; Orom, Nelson, Underwood, Homish, & Kapoor, 2015), improves sleep quality (Lau, Hui, Lam, & Cheung, 2017; Uchino et al., 2016), reduces the risk of suicidal ideation (Chang et al., 2017; Huffmann et al., 2016), diminishes the perceived intensity of postsurgical pain (Hanssen, Peters, Vlaeyen, & Meevissen, 2013, Ronaldson et al., 2014), decreases the risk of coronary heart disease (Kim, Smith, & Kubzansky, 2014), and lowers cardiovascular and all-cause mortality risk (Boehm & Kubzansky, 2012; Kim et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has become very important to perform research about instruments aimed to measure optimism in a valid and reliable manner since optimism is a psychological characteristic associated with many beneficial effects on many spheres of peoplés lives (see a very complete recent review of this topic in Carver & Scheier, 2014), for instance, physical and mental health (Conversano, Rotondo, Lensi, Della-Vista, Arpone, & Reda, 2010), interpersonal relationships (Sumi, 2006), family life (Esfahan & Rostami, 2016; Taylor, Larsen-Rife, Conger, Widaman, & Cutrona, 2010), professional life (Mishra, Patnaik, & Mishra, 2016), and the development of an overall sense of social well-being (Yu & Luo, 2018), More specifically, from a medical perspective, evidence shows that optimism decreases the level of anxiety and depression in cancer patients (Ahmad & Gaber, 2019; Lam et al., 2016; Orom, Nelson, Underwood, Homish, & Kapoor, 2015), improves sleep quality (Lau, Hui, Lam, & Cheung, 2017; Uchino et al., 2016), reduces the risk of suicidal ideation (Chang et al., 2017; Huffmann et al., 2016), diminishes the perceived intensity of postsurgical pain (Hanssen, Peters, Vlaeyen, & Meevissen, 2013, Ronaldson et al., 2014), decreases the risk of coronary heart disease (Kim, Smith, & Kubzansky, 2014), and lowers cardiovascular and all-cause mortality risk (Boehm & Kubzansky, 2012; Kim et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for this situation may be interpreted as a stressful thinking style, which causes hopelessness. Esfahan and Rostami (2016) emphasised that a child with disabilities may have a negative influence on the family, that parents who are hopeful and optimistic about themselves and the world could be healthier mentally and physically and a positive emotional situation could improve mental, psychological and even physical states of the family members. Shenaar-Golan (2017), in her study, noted that in families with children with disabilities, mothers and fathers who had high levels of hope also had high levels of subjective well-being, and improvement in their subjective well-being increased their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in the process which starts with the diagnosis of a disability in the child or having a disabled child, each family with disabled children has different experiences and tries to cope with various issues. It is indicated that families believing that their child would be better with a hopeful and optimistic approach about the future contribute positively to the fulfilment of their roles in the family and to the communication within the family, that persons who are optimistic and hopeful about themselves and their families are healthy in all aspects, that their welfare is positively influenced by the situation (Esfahan & Rostami, 2016) and that their satisfaction in life is improved in this difficult process (Hutz, Midgett, Pacico, Bastianello & Zanon, 2014). Uljarevic, Carrington and Leekam (2016) indicated that when families felt that the situation in which they were in was uncertain, the level of intolerance to uncertainty was high in family members, resulting in increased anxiety.…”
Section: Introductionmentioning
confidence: 99%